Effectiveness of homocysteine lowering vitamins in prevention of thrombotic tendency at high altitude area: A randomized field trial. Issue 4 (October 2015) - Kotwal, Jyoti; Kotwal, Atul; Bhalla, Sandeep; Singh, P.K.; Nair, Velu
Abstract: Introduction: A higher risk of thrombosis has been reported on prolonged stay at high altitude (HAA). Lowering of homocysteine (Hcy) has been found to reduce the risk of venous thrombosis. A randomized field trial was conducted with primary question whether Hcy lowering agents have any effect on the incidence of thrombosis at HAA amongst Indian soldiers as compared to existing interventions. Methods: All units freshly inducted to HAA were randomized into intervention (Vit B12 1000 microgram/day, B6 3 mg/day & folic acid 5 mg/day) and control arms, with a sample size of 12, 000 person-years in each arm. Results: At the end of one year stay at HAA, Folate and B 12 levels decreased significantly in control arm. The levels of Hcy, fibrinogen and plasminogen activator inhibitor (PAI 1) were lower and nitric oxide higher in intervention arm as compared to control arm (p < 0.05). At the end of 2 years, 5 thrombotic episodes occurred in the intervention arm and 17 in control arm with RR of 0.29 (95% CI 0.11-0.80), attributable fraction % (AFe) 70.59%, Population attributable risk percent 54.55% and Protective Fraction 240%. Conclusion: Intervention with B12 and folic acid is effective in reducing Hcy, PAI 1, fibrinogen levels and increasing NO levels at 1 yr as compared to control arm and reducing the incidence of thrombosis at 2 years of stay at HAA. Thus, vitamin B 12, B6 and folic acid intervention is safe and effective method of reducing morbidity and mortality caused by HAA induced coagulopathy. Highlights: Higher risk of thrombosis reported on prolonged stay at high altitude Randomized field trial among healthy individuals Intervention arm (Vit B12 1000 microgram/day, B6 3 mg/day and Folic acid 5 mg/day) After follow up period of two years, RR = 0.29 (95% CI 0.11, 0.80) Intervention effective in reducing incidence of thrombosis at 2 years of stay at HA